Globular structures in roots accumulate phosphorus to extremely high concentrations following phosphorus addition - Ryan, Megan H.; Kaur, Parwinder; Nazeri, Nazanin K.; Clode, Peta L.; Keeble‐Gagnère, Gabriel; Doolette, Ashlea L.; Smernik, Ronald J.; Van Aken, Olivier; Nicol, Dion; Maruyama, Hayato; Ezawa, Tatsuhiro; Lambers, Hans; et al. (Plant, cell and environment, 2019)
Crops with improved uptake of fertilizer phosphorus (P) would reduce P losses and confer environmental benefits. We examined how P‐sufficient 6‐week‐old soil‐grown Trifolium subterraneum plants, and 2‐week‐old seedlings in solution culture, accumulated P in roots after inorganic P (Pi) addition. In contrast to our expectation that vacuoles would accumulate excess P, after 7 days, X‐ray microanalysis showed that vacuolar [P] remained low (<12 mmol kg−1). However, in the plants after P addition, some cortex cells contained globular structures extraordinarily rich in P (often >3,000 mmol kg−1), potassium, magnesium, and sodium. Similar structures were evident in seedlings, both before and after P addition, with their [P] increasing threefold after P addition. Nuclear magnetic resonance (NMR) spectroscopy showed seedling roots accumulated Pi following P addition, and transmission electron microscopy (TEM) revealed large plastids. For seedlings, we demonstrated that roots differentially expressed genes after P addition using RNAseq mapped to the T. subterraneum reference genome assembly and transcriptome profiles. Among the most up‐regulated genes after 4 hr was TSub_g9430.t1, which is similar to plastid envelope Pi transporters (PHT4;1, PHT4;4): expression of vacuolar Pi‐transporter homologs did not change. We suggest that subcellular P accumulation in globular structures, which may include plastids, aids cytosolic Pi homeostasis under high‐P availability. We examined clover roots after inorganic phosphorus (Pi) addition. Although vacuolar P concentration was unchanged, unexpectedly, P accumulated in intracellular globular structures and genes similar to plastid envelope Pi transporters were up‐regulated. The structures likely aid cytosolic Pi homeostasis.